Schizophrenia : the most serious of psychotic disorders - 306303 Goh, Siao Yen; Azizi Yahaya; Association of Psycological and Educational Counsellors of Asia Pacific Biennial International Conference (15th : 2004 : Johor) (Skudai : Universiti Teknologi Malaysia, 2004)
42